Discrepancy in coordination and variation of root and leaf traits among herbaceous and shrub species in the desert, China - Ma, Jing; Wang, Taotao; Wang, Hongyong; Chen, Yiming; Yang, Jie; Xie, Tingting; Shan, Lishan (Frontiers in Plant Science, 2024)
Alterations in life forms could simultaneously influence the variability of fine root and leaf traits. However, our understanding of the organ-level coordination and patterns of variation in fine root and leaf traits among desert herbs and shrubs with distinct habits remains limited. Consequently, this study examined the leaf and fine root traits of 9 shrubs and 9 herbs across three desert habitats. The aim was to identify the hub traits and the resource trade-off strategies employed by desert plants to adapt to their environment. The results showed that the extent of coordination between leaf and root traits, defined as similarity, was contingent upon the life form.While the traits in shrubs were completely decoupled, those in herbs exhibited a high degree of coordination. The traits related to water acquisition and storage are highly connected and do not depend on traits and life forms. Most leaves and fine roots were primarily loaded along the PC1 and PC2 axes of principal component analysis, suggesting that herbs and shrubs each adopt the most advantageous trait syndrome in accordance with their life form to acquire and conserve resources. The leaf economic spectrum and the root economic spectrum evolved independently, showing no dependence on the variations in life form. In conclusion, in desert plants, leaf and root variations occur independently along two axes, with traits associated with water acquisition playing a neutral role in their ecological strategy.